2021
DOI: 10.47176/jafm.14.06.32437
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Dynamic Characteristics and Flow Distribution ‎Structure Optimization of Axial Piston Pump Considering ‎Cavitation Bubble Evolution

Abstract: An axial piston pump can produce a serious cavitation phenomenon in the high-and low-pressure transition process. Cavitation bubbles expand, compress, rebound and collapse when they enter the high-pressure oil drainage area. This affects the outlet flow ripple as well as the pressure pulsation of the piston pump. However, the effect of the cavitation bubbles is ignored in the current outlet flow ripple model of axial piston pumps. It affects the optimization design of the axial piston pump distribution area st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Shi et al (Shi et al, 2020a) designed an axialflow pump impeller based on the surface element method, and studied the influence of the impeller rotor on the hydraulic performance of the all-tube pump, and found that the reduction of the maximum running head of the all-tube pump was greater than that of the axial flow pump. Pan et al (Pan et al, 2021) proposed a method to optimize the hydrodynamic characteristics of axial piston pumps and the structural parameters of the distribution zone considering the evolution of cavitation bubbles. Liang et al (Liang et al, 2018) used CFD numerical simulation technology to optimize the design of the impeller and guide vane body of the tubular pump in order to deeply study the performance of the tubular pump device with rear bulb.…”
Section: Introductionmentioning
confidence: 99%
“…Shi et al (Shi et al, 2020a) designed an axialflow pump impeller based on the surface element method, and studied the influence of the impeller rotor on the hydraulic performance of the all-tube pump, and found that the reduction of the maximum running head of the all-tube pump was greater than that of the axial flow pump. Pan et al (Pan et al, 2021) proposed a method to optimize the hydrodynamic characteristics of axial piston pumps and the structural parameters of the distribution zone considering the evolution of cavitation bubbles. Liang et al (Liang et al, 2018) used CFD numerical simulation technology to optimize the design of the impeller and guide vane body of the tubular pump in order to deeply study the performance of the tubular pump device with rear bulb.…”
Section: Introductionmentioning
confidence: 99%